Notes on the Economic Evaluation of Transport Projects - Mackie, Peter; Nellthorp, John; Laird, James (World Bank, Washington, DC, 2012)
In response to many requests for help in the application of both conventional cost benefit analysis in transport and addressing of the newer topics of interest, we have prepared a series of Economic Evaluation Notes that provide guidance on some of issues that have proven more difficult to deal with. The Economic Evaluation Notes are arranged in three groups. The first group (TRN-6 to TRN-10) provides criteria for selection a particular evaluation technique or approach; the second (TRN-11 to TRN-17) addresses the selection of values of various inputs to the evaluation, and the third (TRN-18 to TRN-26) deals with specific problematic issues in economic evaluation. The Notes are preceded by a Framework (TRN-5), that provides the context within which we use economic evaluation in the transport sector. Economic evaluation involves the assessment of the net value of projects and policies. In the transport sector we value projects in terms of their net worth, the difference between the value of their benefits and their costs, both measured so far as is possible in terms of monetary units. This disarmingly simple statement leads to many questions; evaluation by whom, for whom, from what perspective, at what stage. One of the features of transport decisions is that they typically impact on many parties - transport operators, individual transport users, local residents and businesses, land and property owners, national and local taxpayers.